Adherence to pancreatic enzyme replacement therapy among patients with chronic pancreatitis in East China: a mixed methods study - You Zhou; Ren-Qian Huang; Qi-Wei Wu; Jin-Jie Xu; Jin-Hui Yi; Cui Chen; Guo-Tao Lu; Zhao-Shen Li; Dan Wang; Liang-Hao Hu (Scientific Reports, 2023)
Abstract Pancreatic enzyme replacement therapy (PERT) has been recommended as the preferred method for pancreatic exocrine insufficiency caused by chronic pancreatitis (CP). However, at present, the patient-related factors for the poor PERT management are not clear, and there are no studies on the adherence to PERT in patients with CP in East China. This was a mixed-method study following the principle of sequential explanatory design and included two parts: a quantitative and qualitative study. A cross-sectional survey of medication adherence (MA) was first carried out, followed by a semi-structured interview to further explore and explain the influencing factors of adherence to PERT. Of the 148 patients included in this study, 48.0% had poor MA and only 12.8% had good MA. Multivariate logistic regression showed that lower levels of education and income were contributing factors for non-adherence to PERT. Semi-structured interviews with 24 patients revealed that the reasons for non-adherence also included lack of knowledge, self-adjustment of PERT, lifetime of medication, side effects of PERT, forgetfulness, financial burdens, and accessibility issues. The adherence to PERT was poor among patients with CP in East China. Healthcare providers should personalize medication strategies to improve patients’ MA.